2022
DOI: 10.1101/2022.09.02.506318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microsaccades transiently lateralise EEG alpha activity

Abstract: The lateralisation of 8–12 Hz alpha activity is a canonical signature of human spatial cognition that is typically studied under strict fixation requirements. Yet, even during attempted fixation, the brain produces small involuntary eye movements known as microsaccades. Here we report how spontaneous microsaccades — made in the absence of incentives to look elsewhere — can themselves drive transient lateralisation of EEG alpha power according to microsaccade direction. This transient lateralisation of posterio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…We focused our analysis on spatial biases in gaze shifts (saccades/microsaccades). To identify gaze shifts, we employed a velocity-based method that we established in our prior studies 17,43 , that builds on other velocity-based detection methods (e.g. 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…We focused our analysis on spatial biases in gaze shifts (saccades/microsaccades). To identify gaze shifts, we employed a velocity-based method that we established in our prior studies 17,43 , that builds on other velocity-based detection methods (e.g. 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…The topographic modulation of alpha power (i.e. power reduction) was associated with consistent eye movements towards the contralateral visual hemifield 36-38 . We here set out to test the link between eye movements and alpha/beta activity in the context of episodic memory formation.…”
Section: Introductionmentioning
confidence: 93%
“…The topographic modulation of alpha power (i.e. power reduction) was associated with consistent eye movements towards the contralateral visual hemifield [36][37][38] .…”
Section: Introductionmentioning
confidence: 95%
“…It will thus be important for future research to identify the underlying mechanisms of the observed effects. Potential links to alpha modulations (Liu, Nobre, & Ede, 2022; Liu, Nobre, & van Ede, 2022; Popov et al, 2021, 2022) or arousal states with regards to (sub)cortical neurotransmitter-dependent modulations (Schuerman et al, 2022) could be investigated.…”
Section: Discussionmentioning
confidence: 99%